ANALYZING THE CONTENT OF HISTORY MATERIALS IN THE 2013 CURRICULUM INTEGRATED THEMATIC BOOK FOR PRIMARY SCHOOLS (SD/MI) - Arif Widodo; Dyah Indraswati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The content of history materials should not be ignored in learning at elementary schools. However, in reality, history has always been regarded as a second-level lesson that is not very important. One of the causes is teachers’ ignorance of the educational values contained in the content of history materials. This study aimed to analyze history content in SD/MI thematic books. The object of this study was the 2013 curriculum integrated thematic book revised edition of 2017/2018. The method in this study was content analysis. The values found in the content of history materials at elementary schools included educational, instructive, recreational, and inspirational values. These values were contained in Theme 5 “My Hero” at grade IV, Theme 7 “Events in Life” at grade V, and Theme 3 “Figures and Inventions” at grade VI. In addition, several character values were also found including heroism, nationalism, cooperation, steadfastness, vigilance, and willingness to sacrifice for the sake of the people. This study demonstrated the benefits of studying history for students. The 2013 curriculum integrated thematic book was very suitable to be used as a medium in studying history material at elementary school.